The Economic Burden of Candidemia and Invasive Candidiasis: A Systematic Review - Wan Ismail, Wan Nor Ain; Jasmi, Nadhirah; Khan, Tahir Mehmood; Hong, Yet Hoi; Neoh, Chin Fen (Elsevier, 2020)
Background: Candidemia or invasive candidiasis (IC) is an increasingly common fungal infection and has been associated with high mortality, particularly among the immunocompromised and critically ill. Although several studies have been conducted to estimate the cost of managing candidemia and IC, quality assessment on the methodological aspects of these cost studies was not performed. To date, no systematic review focusing on the economic burden of candidemia and IC has ever been conducted. Objectives: The aim of this study was to systematically review the available evidence on the economic burden of candidemia and IC worldwide. Methods: Databases (ie, PubMed, Scopus, EconLit, HEORO, and Ovid/Embase) were searched through June 2018. Two researchers independently assessed the quality of the eligible studies. Costs reported in the included studies were converted to 2016 USD using Campbell and Cochrane Economics Methods Group-the Evidence for Policy and Practice Information (CCEMG–EPPI)-Centre Cost Converter software. Results: Eight articles were included in this systematic review. The mean total cost per patient with candidemia and IC ranged from $48 487 to $157 574, whereas the mean cost per hospitalization associated with candidemia and IC was from $10 216 to $37 715. All studies were from developed Western countries and reported only direct costs of candidemia and IC. Hospitalization was the main cost driver, contributing to more than half of the total costs. Conclusion: Quality cost studies on candidemia and IC based on standardized methods to provide informed decision making among healthcare authorities in implementing appropriate strategies is anticipated, in particular in developing countries. © 2019 ISPOR--The professional society for health economics and outcomes research